A lightweight and efficient rice field fertilizer applicator: structure, control, and test analysis - Fan, Chengsai; Wan, Shijun; Sun, Jianfu; Xu, Gaoming; He, Ruiyin (Frontiers in Plant Science, 2025)
Side-deep fertilization in paddy fields is key to improving nitrogen use efficiency (NUE) and reducing surface water pollution. However, conventional applicators are overly heavy and incompatible with paddy machinery’s limited horsepower, restricting the technology’s popularization. To solve this, this study had two core goals: develop a lightweight, low-power centrifugal distribution-type side-deep fertilizer applicator matching paddy machinery’s load and horsepower limits; design a dedicated control system to enhance fertilization uniformity and fertilizer adaptability. First, the bulk density-based fertilizer model was improved through theoretical analysis of the external grooved wheel fertilizer discharging device, and its performance was validated in bench experiments. Simultaneously, the centrifugal distribution principle was analyzed, with dispenser rotational speed and discharge rotational speed selected as key factors and uniformity across rows chosen as the response variable. The optimum rotational speed-matching and optimal speed-matching models of the dispenser and distributor were established through CCD testing. The control system of the overall machine integrated both the bulk density-based fertilizer discharge and optimal speed matching models and performed tests in the field. The results showed that the average error in total fertilizer discharge is 4.84%, with a maximum error value of 7.93%, the average coefficient of variation for fertilizer discharge across rows was 5.47%, with a maximum coefficient of variation of 7.03%. Furthermore, comparative analyses revealed that the control system adapted well to different fertilizers and maintained stability between static and dynamic tests, thereby indicating strong dynamic adaptability. Compared with other fertilizer applicators for paddy field machinery, this device offers evident advantages in terms of quality, cost, and horsepower requirements, highlighting its potential for widespread adoption.